1996
DOI: 10.1002/j.2161-1912.1996.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling for Dropout Prevention: Applications From Multicultural Counseling

Abstract: Although high school dropout rates have declined over the past several years, rates remain high for many segments of our population. Most of the attention devoted to dropout prevention counseling has focused on group counseling or programmatic issues, whereas individual counseling has largely been ignored. This article draws on commonalities between multicultural counseling and dropout prevention to produce a general framework for individual counseling with students who have potential to drop out of high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Participants noted that changing their own motivations and a more flexible stance on the part of the school regarding work would have helped them stay in school. These findings are consistent with two studies describing cultural and cognitive flexibility as effective student responses to obstacles to school completion (Pang & Barba, 1995;Trusty, 1996). Overall, however, participants seemed to have little specific knowledge of how to affect the school system or how to stay in, reflecting the misunderstandings discussed above.…”
Section: Group Group Group Group Group Themessupporting
confidence: 88%
See 1 more Smart Citation
“…Participants noted that changing their own motivations and a more flexible stance on the part of the school regarding work would have helped them stay in school. These findings are consistent with two studies describing cultural and cognitive flexibility as effective student responses to obstacles to school completion (Pang & Barba, 1995;Trusty, 1996). Overall, however, participants seemed to have little specific knowledge of how to affect the school system or how to stay in, reflecting the misunderstandings discussed above.…”
Section: Group Group Group Group Group Themessupporting
confidence: 88%
“…Note that the suspension rates for Whites are decreasing (De La Rosa & Maw, 1990). Researchers have suggested that a cultural mismatch between student and school may result in alienation or drop out from school (Pang & Barba, 1995;Trusty 1996).…”
mentioning
confidence: 99%